La fertilización del frijol (Phaseolus sp.) - FASSBENDER, H.W. (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
The objective of the present work is to revise the existing literature on fertilization of beans to be applied to the program of bean improvement in the Inter-American Institute of Agricultural Science. The various nutritional requirements of the bean plant are considered together with fertilization where soils are not able to supply them. Fertilization with nitrogen, phosphorus, potassium and other elements in Latin America and some experimental stations in U.S.A. is presented and discussed. Considering the lack of sufficient data in Central America, where this study is to be carried out, it is proposed to make a study of the soils of bean producing areas. The various steps to be followed in the planning of these studies are also presented.